1990
DOI: 10.1021/bi00488a037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the antitumor drug cis-diamminedichloroplatinum(II) and related platinum complexes on eukaryotic DNA replication

Abstract: An SV40-based in vitro replication system has been used to examine the effects of platinum compounds on eukaryotic DNA replication. Plasmid templates containing the SV40 origin of replication were modified with the anticancer drug cis-diamminedichloroplatinum(II) (cis-DDP, cisplatin) or the inactive analogues [Pt(dien)Cl]+ and trans-DDP. The platinated plasmids were used as templates for DNA synthesis by the DNA polymerases present in cytosolic extracts prepared from human cell lines HeLa and 293. Bifunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 20 publications
4
57
1
1
Order By: Relevance
“…The lethal effects of adozelesin in mammals occur in a cell cycle-specific and proliferation-dependent pattern that is essentially identical to that observed in orc2-1 and wild type S. cerevisiae cells treated with this drug: very sensitive in G 1 , less sensitive in S phase, and least sensitive in G 2 /M and G 0 (11,12). The G 0 resistance is particularly interesting, because a similar relationship between proliferative capacity and cytotoxic or apoptotic response has been observed with other DNA damaging agents and antitumor drugs (40,41), at least one of which, like adozelesin, has been shown to specifically inhibit initiation of DNA replication (42). In the context of the high degree of conservation of ORC proteins and other components of the origin licensing apparatus and the intra-S-phase DNA damage checkpoint, the G 1 -specific cytotoxic effects of adozelesin and other antitumor drugs in mammals may be caused by a similar ORC-dependent response that inactivates origin licensing.…”
Section: Adozelesin and Inhibition Of Initiation Of S Cerevisiae Dnamentioning
confidence: 82%
“…The lethal effects of adozelesin in mammals occur in a cell cycle-specific and proliferation-dependent pattern that is essentially identical to that observed in orc2-1 and wild type S. cerevisiae cells treated with this drug: very sensitive in G 1 , less sensitive in S phase, and least sensitive in G 2 /M and G 0 (11,12). The G 0 resistance is particularly interesting, because a similar relationship between proliferative capacity and cytotoxic or apoptotic response has been observed with other DNA damaging agents and antitumor drugs (40,41), at least one of which, like adozelesin, has been shown to specifically inhibit initiation of DNA replication (42). In the context of the high degree of conservation of ORC proteins and other components of the origin licensing apparatus and the intra-S-phase DNA damage checkpoint, the G 1 -specific cytotoxic effects of adozelesin and other antitumor drugs in mammals may be caused by a similar ORC-dependent response that inactivates origin licensing.…”
Section: Adozelesin and Inhibition Of Initiation Of S Cerevisiae Dnamentioning
confidence: 82%
“…Amounts of MC and Pt(II) interstrand crosslinks in the cell DNA are 2-10%, compared to 90% or more intrastrand crosslinks. Therefore, the XPA cells can tolerate a great amount of monoadducts and intrastrand crosslinks by the replication-dependent or postreplication repair pathway, even though the major d(GpG) intrastrand crosslinks effectively block replication in vitro (Ciccarelli et al, 1985;Heiger-Bernays et al, 1990;Lemaire et al, 1991;Iwata et al, 1991). In consequence, interstrand crosslinks are more potentially lethal than intrastrand adducts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DWA2114R appears to be a promising new analog. Both Pt(II) intra-and interstrand crosslinks formed at the specific DNA sequences block DNA synthesis in vitro (Heiger-Bernays et al, 1990;Lemaire et al, 1991;Iwata et al, 1991) and in vivo (Roberts & Friedlos, 1987), and inhibit RNA transcription in vitro (Corda et al, 1991) at damaged sites. Some studies have indicated that the main cytotoxic lesions are abundant Pt(II) intrastrand crosslinks (HeigerBernays et al, 1990;Lepre & Lippard, 1990), while the others have indicated that the minor Pt(II) interstrand crosslinks are more lethal (Knox et al, 1986;Roberts & Friedlos, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that their mechanism of action might be different from that of cis-DDP and might involve a biological processing of the monoadducts. Platinum mono and diadducts are repaired in prokaryotic and eukaryotic cells (2,(11)(12)(13)(14)(15)(16)(17)(18). Recent studies on trans-1,2-diaminocyclohexanedichloroplatinum(II), which is also characterized by a bulky nonexchangeable ligand, revealed that monoadducts were more efficiently repaired than diadducts by UvrABC excinuclease (14).…”
mentioning
confidence: 99%